Endocycle-related tubular cell hypertrophy and progenitor proliferation recover renal function after acute kidney injury - Lazzeri, Elena; Angelotti, Maria Lucia; Peired, Anna; Conte, Carolina; Marschner, Julian A.; Maggi, Laura; Mazzinghi, Benedetta; Lombardi, Duccio; Melica, Maria Elena; Nardi, Sara; Ronconi, Elisa; Sisti, Alessandro; et al. (Nature communications, 2018)
Acute kidney injury (AKI) is considered largely reversible based on the capacity of surviving tubular cells to dedifferentiate and replace lost cells via cell division. Here we show by tracking individual tubular cells in conditional Pax8/Confetti mice that kidney function is  recovered after AKI despite substantial tubular cell loss. Cell cycle and ploidy analysis upon AKI in conditional Pax8/FUCCI2aR mice and human biopsies identify endocycle-mediated hypertrophy of tubular cells. By contrast, a small subset of Pax2+ tubular progenitors enriches via higher stress resistance and clonal expansion and regenerates necrotic tubule segments, a process that can be enhanced by suitable drugs. Thus,  renal functional recovery upon AKI involves remnant tubular cell hypertrophy via endocycle and limited progenitor-driven regeneration that can be pharmacologically enhanced. The recovery of function upon acute kidney injury is thought to involve tubular cell dedifferentiation and proliferation. Here the authors show that Pax2+ progenitors regenerate tubules via cell division while other tubular cells support function recovery by undergoing hypertrophy through endoreplication.